Understanding Chylomicron Retention Disease Through Sar1b Gtpase Gene Disruption: Insight From Cell Culture. Issue 12 (December 2017) - Sané, Alain Théophile; Seidman, Ernest; Peretti, Noel; Kleme, Marie Laure; Delvin, Edgard; Deslandres, Colette; Garofalo, Carole; Spahis, Schohraya; Levy, Emile
Abstract : Background—: Understanding the specific mechanisms of rare autosomal disorders has greatly expanded insights into the complex processes regulating intestinal fat transport. Sar1B GTPase is one of the critical proteins governing chylomicron secretion by the small intestine, and its mutations lead to chylomicron retention disease, despite the presence of Sar1A paralog. Objective—: The central aim of this work is to examine the cause–effect relationship between Sar1B expression and chylomicron output and to determine whether Sar1B is obligatory for normal high-density lipoprotein biogenesis. Approach and Results—: The SAR1B gene was totally silenced in Caco-2/15 cells using the zinc finger nuclease technique. SAR1B deletion resulted in significantly decreased secretion of triglycerides (≈40%), apolipoprotein B-48 (≈57%), and chylomicron (≈34.5%). The absence of expected chylomicron production collapse may be because of the compensatory SAR1A elevation observed in our experiments. Therefore, a double knockout of SAR1A and SAR1B was engineered in Caco-2/15 cells, which led to almost complete inhibition of triglycerides, apolipoprotein B-48, and chylomicron output. Further experiments with labeled cholesterol revealed the downregulation of high-density lipoprotein biogenesis in cells deficient in SAR1B or with the double knockout of the 2 SAR1 paralogs. Similarly, there was a fall in the movement of labeled cholesterol from cells to basolateral medium containing apolipoprotein A-I, thereby limiting newly synthesized high-density lipoprotein in genetically modified cells. The decreased cholesterol efflux was associated with impaired expression of ABCA1 (ATP-binding cassette subfamily A member 1). Conclusions—: These findings demonstrate that the deletion of the 2 SAR1 isoforms is required to fully eliminate the secretion of chylomicron in vitro. They also underscore the limited high-density lipoprotein production by the intestinal cells in response to SAR1 knockout. Abstract : Supplemental Digital Content is available in the text.